Fluid Volume Status Assessment by Lung Ultrasonography in Patients with Kidney Disease. - Saigal, Navid (Pakistan Journal of Kidney Diseases, 2021)
Point-of-care ultrasound (POCUS) has become firmly established in acute and critical care settings and has now emerged as an important tool in the assessment of the Extra Vascular Lung Water (EVLW). Lung ultrasound (LUS) can be performed quickly and easily in critically ill patients. It has a higher diagnostic accuracy than physical examination and chest radiography combined. It enhances safety by avoiding ionizing radiation and the need for potentially dangerous transfers within the hospital. LUS can also be used to guide fluid management.